O22-6 Occupational exposure to organochlorine insecticides and prostate cancer risk in agrican. (1st September 2016) - Lemarchand, Clémentine; Tual, Séverine; Boulanger, Mathilde; Carles, Camille; Levêque-Morlais, Noémie; Stéphanie, Perrier; Clin, Bénédicte; Guizard, Anne-Valérie; Velten, Michel; Marcotullio, Elisabeth; Baldi, Isabelle; Lebailly, Pierre
Abstract : Introduction: Farming and pesticide use have been repeatedly and consistently associated with prostate cancer risk but analysis on the role of specific active ingredients remain scarce and results inconclusive. We assessed associations between occupational exposure to specific organochlorines and prostate cancer in the agricultural cohort AGRICAN. Methods: The AGRICAN cohort consisted of 181, 842 participants, affiliated for at least 3 years to the French agricultural health insurance. Data on pesticide use on 6 crops, including years of beginning and ending, were collected from the enrolment questionnaire. Exposure to organochlorine insecticides and duration of exposure between 1950 and 2010 was assessed with the help of a crop-exposure matrix (PESTIMAT). Associations with prostate cancer were estimated using a Cox regression analysis with attained age as time scale. Results: From enrolment (2005–2007) to 2009, 1 672 incident prostate cancer cases among 98, 974 male participants were identified through linkage with cancer registries. A nearly significant increase in prostate cancer risk was observed when considering organochlorines as a group (HR 1.15, 95% CI: 0.99–1.32; 463 cases) with no linear relationship with duration of exposure. A significant association was observed for eight individual organochlorine pesticides (out of 18) and a significant relationship with duration of exposure was observed for 6 of them (aldrin, chlordane, dieldrin, DDD, toxaphene and HCH). When adjusting for exposure to the 5 other organochlorines, a greater prostate cancer risk remained among men with the highest duration of exposure to HCH and DDD. Conclusions: Our study provides new results concerning the association between pesticide exposure and prostate cancer, especially for two organochlorines: DDD (a DDT metabolite) and HCH (a mix of isomers including γ-HCH also called lindane).